Study of clitoral hood anatomy in the pediatric population. Issue 3 (June 2016) - Brodie, K.E.; Grantham, E.C.; Huguelet, P.S.; Caldwell, B.T.; Westfall, N.J.; Wilcox, D.T.
Summary: Introduction and aims: Pediatric female genitalia size and morphology have not previously been well described. The aims of this study were to create a standard reference for the anterior vulval structures, and examine the relationship between the clitoral hood and labia minora. Method: Female patients between 0 and 16 years of age, and with normal external genitalia had the following measurements taken: length of clitoral hood, length of sides of clitoral hood, clitoral diameter, apex of clitoral hood to base of pubic symphysis, apex of clitoral hood to urethral orifice, distance of clitoral hood to labia majora, and length and depth of labia minora. Qualitative descriptors of the clitoral hood and labia were recorded. Patients were grouped into age ranges for analysis: 0–3 years, 4–8 years, 9–12 years, and 13–16 years. Results: Fifty-eight girls were examined. There was a linear relationship between age and genital structure size. In the majority of patients, the labia minora converged under the clitoral glans, separate to the clitoral hood. Four shapes of clitoral hood were observed: horseshoe, trumpet, coffee bean, and tent. Discussion: This study observed great variation in size and morphology of pediatric female genitalia, which is in keeping with other studies. The study was limited by ability to recruit older patients to the study (girls aged 11–16 years) and, therefore, there were lower numbers in this age category. However, the trends that were observed were present in both younger and older girls. Conclusion: External genitalia size and morphology are varied in the pediatric female population. The clitoral hood and labia minora were observed to be distinctly separate structures. This study provides a reference for surgeons undertaking genital reconstruction procedures. The study demonstrated that the clitoral hood and labia minora are anatomically distinct structures. Age category measurement (mm) 0–3 years ( n = 18) 4–8 years ( n = 18) 9–12 years ( n = 9) 13–16 years ( n = 13) Mean length of clitoral hood 8.7 14.3 16.9 20.9 Mean clitoral diameter 2.5 3.4 3.9 4.5 Length of sides of clitoral hood 21.6 36.2 47.8 56.4 Clitoral hood to pubic symphysis 14.7 27.6 34.6 44.5 Clitoral hood to labia majora 2.3 3.0 6.4 6.8 Clitoral hood to urethral orifice 12.4 17.1 24.8 39.4 Length of labia minora 9.4 10.7 15.2 40.0 Depth of labia minora 3.5 3.6 3.9 12.2